2022
DOI: 10.1007/s10648-022-09671-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8 Weeks with Embodied Learning on 5–6-Year-Old Danish Children’s Pre-reading Skills and Word Reading Skills: the PLAYMORE Project, DK

Abstract: The aim of this study was to investigate the effects of embodied learning on children’s pre-reading and word reading skills. We conducted a three-armed randomized controlled trial including two intervention groups and one control group. One hundred forty-nine children from grade 0 (5–6 years old) who had just started school were recruited from 10 different classes from four elementary schools. Within each class, children were randomly assigned to receive teaching of letter-sound couplings and word decoding eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…In line with this idea, previous studies have shown that handwriting interventions are more efficient when they involve letter tracing compared with only perceptuo-motor training (Hoy et al, 2011;Santangelo & Graham, 2016). In addition, recent studies have reported that the addition of gross and fine motor activities during letter and word learning improves letter knowledge more than traditional instruction in kindergarteners and first graders (Bara & Bonneton-Botté, 2017;Botha & Africa, 2020;Damsgaard et al, 2022). These studies support the added value of motor interventions combined with language intervention.…”
Section: Limitations and Future Directionsmentioning
confidence: 55%
“…In line with this idea, previous studies have shown that handwriting interventions are more efficient when they involve letter tracing compared with only perceptuo-motor training (Hoy et al, 2011;Santangelo & Graham, 2016). In addition, recent studies have reported that the addition of gross and fine motor activities during letter and word learning improves letter knowledge more than traditional instruction in kindergarteners and first graders (Bara & Bonneton-Botté, 2017;Botha & Africa, 2020;Damsgaard et al, 2022). These studies support the added value of motor interventions combined with language intervention.…”
Section: Limitations and Future Directionsmentioning
confidence: 55%
“…So, to observe a transfer effect from T1 to T2 on word reading, the children participating in the 8-week intervention would have had to acquire letter-sound knowledge proficiency and translate their newly gained knowledge into a basic word reading strategy. However, only 4% of all children acquired basic word reading skills during the intervention period and at T3, 7-8 months after school starts, the proportion had risen to 29% (Damsgaard et al, 2022). This pattern could explain why a transfer effect to word reading were only seen at T3.…”
Section: Discussionmentioning
confidence: 96%
“…This would involve the use of movements to represent the learnt letter forms and sounds. Such approach has been found to be more beneficial for letter recognition and letter-sounds knowledge compared to the standard school curriculum for 6-7-year olds (Damsgaard et al, 2020(Damsgaard et al, , 2022. However, the cognitive mechanisms behind the advantages of embodied learning for pre-reading skills are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…The types of interventions categorized under the label motor activity-based learning have the goal of using the motor system to (1) learn procedures and (motor) skills (e.g., Rabattu et al, 2023; for an overview, see Mavilidi et al, 2018) and (2) to use the motor system to enact, understand, or mentally connect otherwise abstract content (e.g., Amico & Schaefer, 2021;Cherdieu et al, 2017;Damsgaard et al, 2022;Parrill et al, 2023;Smyrnis et al, 2022;Yohannan et al, 2022;. Often, embodied learning interventions are designed to convey declarative knowledge, but can be targeted at motor learning.…”
Section: Motor Activity-based Learningmentioning
confidence: 99%